ANALISIS NILAI TAMBAH DALAM RANTAI PASOK SALAK: STUDI KASUS : KECAMATAN SUMBEREJO, KABUPATEN TANGGAMUS, PROVINSI LAMPUNG - Sihombing, Tulus Martua; Adriant, Irayanti; Ramadhani, Talitha Nirmala (LP2M Universitas Bina Bangsa, 2025)
Indonesia, as a tropical country with a significant agricultural sector, is supported by abundant natural resources. Salak fruit is a major commodity in the supply chain involving farmers, small collectors, large collectors, and retailers. Farmers' incomes are low due to various factors. This research aims to increase the income of actors in the salak supply chain in Sumberejo District, Lampung. The analysis methods used include value chain, added value (Hayami), and financial evaluation (NPV, Net B/C Ratio, Gross B/C Ratio, IRR, and Payback Period). In the value chain analysis in Sumberejo District, the main role of actors was identified, with farmers as the key in cultivation. Small collectors collect and deliver fruit, large collectors are responsible for collection, cleaning, and delivery to retailers. This reflects the specific role of each actor in the salak fruit production value chain. The added value varies in the supply chain, where farmers provide the highest value of Rp 20,947/kg with a profit of Rp 5,216/kg, while retailers provide the lowest value of Rp 580/kg with a profit of Rp 480/kg. This difference reflects the economic contribution of each actor. Processing salak fruit into chips, dodol, and sweets provides additional benefits, with salak dodol rated as the most profitable alternative based on financial evaluation. Dodol Salak's investment shows a satisfactory rate of return (IRR 92%), NPV of IDR 13,696,413, Net B/C of 3.97, Gross B/C of 1.23, and Payback Period of 2 years. Therefore, developing a dodol salak business is a wise step